Vita Activa: The Spirit of Hannah Arendt - Ushpiz, Ada (Israel, Canada, 2015)
The German-Jewish philosopher Hannah Arendt caused an uproar in the 1960s by coining the subversive concept of the "Banality of Evil" when referring to the trial of Adolph Eichmann. This documentary, with its abundance of archival materials, offers an intimate portrait of the whole of Arendt's life.
Language: German, English, and Hebrew.
Keywords: Documentary films